Food analytical and sampling conference of codex alimentarius committee of WHO/FAO in Budapest = A WHO/FAO Codex Alimentarius Bizottságának élelmiszer-analitikai és mintavételi konferenciája Budapesten - Szunyogh Gábor (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2016)
The Codex Alimentarius Commission was established by the Food and Agriculture Organization of the United Nations and the World Health Organization (WHO) in 1963. Documents and analytical standards developed by the Codex serve as the basis for regional and national food regulations, but they are not necessarily binding. At the same time, they provide great help in planning food compliance tests prior to international food transactions. Hungary has been an active participant in the work since 1963, and the annual sessions of the Codex Committee Measurement Analysis and Sampling (CCMAS) have been organized by Hungary since 1972. For the seventh year, WESSLING Hungary Kft., a company operating independent laboratories, has been co-organizer of the event, together with the National Food Chain Safety Office (NÉBIH). © 2016, Hungarian National Commiteee of the European Organization for quality. All rights reserved.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék